Geophysical phenomena and the Alexandrian littoral - Evelpidou, Niki (Archaeopress Publishing Ltd., 2019)
Alexandria is located on the Mediterranean coast of Egypt, bordered by Egypt's Western Desert and the fertile Nile Delta. For many centuries, Alexandria was the major port city in the Eastern Mediterranean and it has been repeatedly struck by natural disasters, such as earthquakes, tsunamis and land subsidence, in its 2400-year history. This book focuses on the geomorphological and archaeological evidence on the coastal zone of Alexandria, attempting to provide a comprehensive review of its evolution, taking into consideration long-term and short-term factors. The book provides an extensive background on the geomorphology and recent geoarchaeological history of Alexandria, discussing historical maps and natural disasters.